American College Students' Knowledge, Perceptions, and Purchasing Habits of Organic Food. Issue 1 (18th December 2015) - Alexander, Nicki E.; Duncan, Dennis; Fuhrman, Nicholas
Abstract : Although there has been a respectable amount of research on consumers' opinions about organic food and their purchasing behavior, the college student demographic has not been thoroughly investigated. The university demographic is an important one, as the students are beginning to make their own food purchasing decisions. Previous research indicates that college students have positive attitudes toward organic food, as well as other alternative production practices. The purpose of this study was to determine college students' knowledge, perceptions, and purchasing habits of organic foods at a southern land‐grant university. Results indicated that of the total food goods purchased by students, 62% of students bought 1 to 25% organic food, almost 16% bought 0% organic food, and almost 16% bought 51 to 75% organic food. Additionally, students' responses suggest that they are most motivated to purchase organic food for their own benefits, vs. to benefit the environment or farmers or workers. No significant difference was found among male and female students' organic food purchasing habits. Although students are impacted by the behaviors and opinions of their parents and peers, parents played a larger role than peers in impacting college students' organic food purchasing habits.